VIDEO INTERAKTIF PEMBELAJARAN MATEMATIKA DENGAN KONTEKS KEMARITIMAN SEBAGAI MEDIA PEMBELAJARAN MENDALAM UNTUK SISWA SMP KELAS VIII - Geeraldin Claudya Sembiring, Octavina; Izzati, Nur; Fera, Mirta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics learning in junior high schools continues to face challenges in implementing deep learning, particularly due to the limited availability of technology-based learning media that provide meaningful learning experiences. Although interactive learning videos have been widely developed, studies integrating maritime contexts with the principles of deep learning in mathematics instruction remain limited. This study aimed to develop an interactive mathematics learning video incorporating a maritime context as a deep learning medium for Grade VIII junior high school students. The study employed a Research and Development (R&D) approach adapted from the ADDIE model, consisting of the Analysis, Design, Development, Implementation, and Evaluation stages. The product was validated by media, material, and language experts and its practicality was evaluated by two mathematics teachers and 47 Grade VIII students. The results indicated that the developed learning video achieved a very valid category, with an overall validity score of 93.04%, comprising 92.08% for the media aspect, 92.59% for the material aspect, and 94.44% for the language aspect. The practicality test also showed that the product was very practical, with an overall practicality score of 93.16%, consisting of 98.89% from teachers' responses and 87.42% from students' responses. The novelty of this study lies in the integration of maritime contexts and deep learning principles into an interactive learning video developed using Powtoon and Edpuzzle, thereby supporting meaningful, engaging, and technology-enhanced mathematics learning. Research findings indicate that the developed instructional video is suitable for trial use in teaching the Pythagorean theorem to Grade 8 junior high school students. Further research is recommended to examine the effectiveness of the product in improving students' conceptual understanding and learning outcomes